Prof. R.P.K. Singh (SPARK), Suryabansh Singh and Sugreev Singh (Farmers)- Rambad, Bihar, India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
The village elders of the Rambad village in India describe how the climate change and the lack of floods are affecting the village and the agriculture and how they are struggling to continue to farm their land. But as the village elders themselves say:"agriculture is our tradition and the earth is our mother: we can't leave it". However, agriculture has become a more unpredictable activity for them, and the villagers can never be sure of what will come increasing food insecurity.